Hugo Klajn - A Pioneer of Social Pathology in Serbia - Trebješanin, Žarko M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
Many of the pioneers, founders, and early builders of social pathology in our country, as well as their contributions, are little known or almost unknown to the wider professional public today. One of these commendable pioneers is certainly our great scientist and cultural creator, Hugo Klajn, whose work in the field of social psychiatry (now sociology of mental disorders) is related to the first half of the twentieth century. The paper is devoted to Klajn’s study of partisan neurosis, which thoroughly and comprehensively interprets the clinical picture, dynamics, and pathogenesis of a new form of neurosis, until then unspecified. But his theoretical and methodological exemplary study of war neurosis goes beyond the scope of scientific and professional work. It is also a precious discussion on human nature in extreme conditions, with a much wider cultural, anthropological, and humanistic meaning. Therefore, we should not forget that Klajn’s in-depth analysis reveals that war neuroses are “a form of rebellion against circumstances that force people to fight” and that “it is necessary to treat not only neurotics, but also societies and the world in which neurotics live”. Because of all these contributions of Hugo Klajn to our social psychology and social pathology, and because of his shrewdness and critical thought, he is a significant and actual theoretician and researcher of our time, as well. In his work and way of thinking, even today, we ought to seek inspiration and clues for solving our own contemporary sociological and sociopathological problems.